SOS Titanic - Bunting, Eve. (New York : Scholastic, 1996)
Fifteen year-old Barry O'Neill travelling from Ireland to America on the maiden voyage of the Titanic, finds his life endangered when the ship hits an iceberg and begins to sink.
Keywords: Ocean liners -- Fiction; Shipwrecks -- Fiction; Titanic -- Fiction